A full-length 16S survey using Nanopore sequencing to uncover the bacterial microbiome in Ixodes ricinus ticks from a single UK woodland, collected across three springs (2019-2021) - Mia L. White; Jack M. Crook; Kayleigh M. Hansford; Daniel P. Carter; Michael J. Elmore; Colin Johnston; Sara Gandy; Kuiama Lewandowski; Alexander Vaux; Karen L. Osman; Richard Vipond; Jolyon M. Medlock; et al. (Ticks and Tick-Borne Diseases, 2025)
Ixodes ricinus is a key vector of several bacterial pathogens, including Borrelia and Rickettsia species. To assess bacterial prevalence and diversity, we characterised the microbiome of ticks collected from a single UK woodland, comparing different woodland types, life stages (adult male, female, and nymph), and sampling years (spring 2019–2021). Unlike previous studies that target short regions of the 16S rRNA gene, we used Nanopore sequencing to generate full-length 16S reads, allowing for higher taxonomic resolution. Our results showed significant microbiome differences across life stages, but not by woodland type or year. Rickettsia was the most abundant taxon, with prevalence varying by life stage and year. Borrelia was present in all life stages but absent in 2021 samples. Anaplasma abundance varied significantly by year and life stage, peaking in nymphs from Pine woodland. Bartonella was found across all woodland types, with the highest abundance in nymphs from Oak-dominated areas.